2016
DOI: 10.12891/ceog3048.2016
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of maternal anxiety on non-stress test parameters

Abstract: Objective: To determine the association between antenatal maternal anxiety with non-stress test (NST) parameters, which is an indicator test of fetal well-being in the third trimester. Materials and Methods: Between January and December of 2013, 212 pregnant women, with 36-41 weeks of gestation were assessed with measures of distress and anxiety with Beck Anxiety Inventory (BAI) and with NST. The new National Institute Child Health and Human Development (NICHD) 2008 guideline criteria were used for interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In our study, the fetal records were more likely to be reactive, and the baseline FHR was higher in the 2 intervention groups compared with the control group. These results are consistent with other studies that showed that the anxiety experienced by pregnant women significantly affects the NST, showing a decreased FHR variability and fewer FHR accelerations the NST 7,29,30 . Under conditions of anxiety, NSTs are more likely to be nonreactive, leading to unnecessary interventions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the fetal records were more likely to be reactive, and the baseline FHR was higher in the 2 intervention groups compared with the control group. These results are consistent with other studies that showed that the anxiety experienced by pregnant women significantly affects the NST, showing a decreased FHR variability and fewer FHR accelerations the NST 7,29,30 . Under conditions of anxiety, NSTs are more likely to be nonreactive, leading to unnecessary interventions.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with other studies that showed that the anxiety experienced by pregnant women significantly affects the NST, showing a decreased FHR variability and fewer FHR accelerations the NST. 7,29,30 Under conditions of anxiety, NSTs are more likely to be nonreactive, leading to unnecessary interventions. Thus, we find that the use of music therapy and VR are useful techniques for relieving the anxiety of pregnant women during tests that generate an external source of anxiety, such as the NST.…”
Section: Discussionmentioning
confidence: 99%